Extracellular polysaccharide-facilitated selenium nanoparticle assembly and metabolic reprogramming support efficient selenite biotransformation by ARTP-mutagenized Lactiplantibacillus plantarum Vse252 - Lihui Tan; Xinyan Wang; Lin Hu; Xiang Gen; Shirui Yu; Xue Li; Xinyu Yan; Bo He; Jun Zhang; Yongzhong Wang; Hengqian Lu (Bioresource Technology, 2026)

Odour concentrations prediction for the rubber industry based on the key odorous substances screening and machine learning - Jing Wang; Xiande Xiao; Jie Meng; Zhiqiang Lu; Zhiyang Zhang; Gen Wang; Boyu Jing; Zengxiu Zhai; Bo Ma; Hao Zhang; Peifang Ren (Journal of Environmental Sciences, 2026)

Mango peel pectin as a high-ester emulsifier for carotenoid delivery: Structural characterization and application in low-fat ice cream - Teng-Gen Hu; Huan Zhang; Lu Li; Yu-Qing Hu; Jing Wen; Bo Zou; Jian Peng; Li-Na Cheng; Ji-Jun Wu; Geng-Sheng Xiao; Yu-Juan Xu; Yuan-Shan Yu (Carbohydrate Polymers, 2026)

MSCAM-DenseNet-based spoofing interference situation awareness for GNSS-based on train localization - Jin Gao; Jiang Liu; Bai-gen Cai; Jian Wang; De-biao Lu; Wei Jiang (GPS Solutions, 2026)

Theta-aurora dynamics: Ionospheric mapping of evolving magnetospheric plasma boundaries - Xin-Ming Chen; Zan-Yang Xing; Qing-He Zhang; Yong-Liang Zhang; Hui-Gen Yang; L. R. Lyons; K. Oksavik; S. E. Milan; Rui-Long Guo; Tong Xu; Bin-Bin Tang; Xiang-Yu Wang; et al. (Science China Earth Sciences, 2026)
The theta-aurora, an auroral feature bridging the nightside and dayside auroral oval under a northward interplanetary magnetic field (IMF), is closely linked to the energetic plasma evolving within the magnetosphere. While existing views emphasize that energetic plasma resides on closed field lines, the mechanism by which it is accelerated and precipitates on open field lines to form the theta aurora remains poorly understood. Here, we introduce a mechanism derived from multi-instrument observations of theta-aurora evolution in the Northern Hemisphere and simulations conducted using a global magnetohydrodynamics (MHD) model. The observations and simulations exhibit excellent agreement, revealing that the theta-aurora represents ionospheric projections of boundaries between distinct magnetospheric plasma. These different magnetospheric plasma, an energetic structure originating from the plasma sheet and the preexisting cold lobe plasma, develop a boundary with contrasting physical properties that drive localized plasma instabilities. Particle precipitation occurs at plasma boundary, and controls both the formation and temporal evolution of theta-aurora. Our findings provide critical insights into the coupling between the ionosphere and magnetosphere under northward IMF.

The application of Milankovitch cycles in determining provenance direction - Ting-yu Zhang; Hui Xue; Ming-guang Hu; Min-shu Wang; Gen Li; Zhen Lu (Applied Geophysics, 2026)

High-voltage-tolerant zirconium-organic nanosheet separator enabling 5 V LiNi0.5Mn1.5O4|Li batteries with enhanced capacity density - Jian-Qiang Shen; Ya-Nan Gao; Ying-Li Song; Lingjuan Zhang; Gen Chen; Guoqiang Tan; Yunfeng Lu; Xian-Ming Zhang (Chemical Engineering Journal, 2026)

Quercetin protects against 17α-methyltestosterone induced hepatocardiac toxicity: Roles of lipid metabolism, oxidative stress, and inflammation - Lu Cao; Yibo Jia; Gen Chen; Chang Hu; Qinyi Wang; Yiqun Han; Huiman Zhang; Shangyun Li; Tongyao Li; Haiyan Zhao; Zijun Xiong; Jing Song; et al. (Aquaculture, 2026)

The ecotoxicological effects of thiamethoxam on photosynthesis and nitrogen fixation in cyanobacteria: From inhibition to recovery - Jiale Zhang; Shiye Zhu; Xiyan Xu; Youzheng Chai; Jihai Shao; Gen Lu; Jianhua Zeng; Ma Bai; Anwei Chen (Journal of Environmental Sciences, 2026)

Synergistic effects of polystyrene microplastics and 17α-methyltestosterone on immune and oxidative stress responses in the gill and liver of Gobiocypris rarus - Yibo Jia; Lu Cao; Tongyao Li; Haiyan Zhao; Gen Chen; Zijun Xiong; Weiya Rong; Qing Liu; Weiwei Wang; Jing Song; Xianzong Wang; Yu Liu; et al. (Fish & Shellfish Immunology, 2026)

High-efficiency restoration of stone cultural relics via immobilized carbonic anhydrase on magnetic graphite oxide - Yaofeng Hu; Yifan Gui; Wei Li; Cuiling Gong; Ziqi Hou; Tong Shu; Ya Wu; Gen Lu; Longjiang Yu (Bioresource Technology, 2026)

Decoupled Global Trends in Zinc Deficiency–attributable Burden (GBD CRA) and Depressive Disorders, 1990–2021: a GBD 2021 Analysis - Chenqi Li; Hongtao Lu; Qicheng Zhou; Yicui Qu; Mengyu Cai; Wenjing Shi; Yinyin Zhang; Gen Miao; Yuxiao Tang; Hui Shen; Biao Gao (Biological Trace Element Research, 2026)

Research on Fracture Characteristics and Crack Propagation Patterns of Freeze-Thaw Damaged Rock Under Loading - Ding Ma; Mei-lu Yu; Lin-kai He; Zhong-wen Wang; Zi-yi Yang; Gen-shui Wu (Applied Geophysics, 2026)

A high-strength, heat-resistant, recyclable, and degradable ramie fiber-reinforced polyimine biocomposite - Pandeng Li; Tingting Liu; Gen Lu; Tong Shu; Tianyi Yu; Yuchen Zhao; Hengwei Fu; Junqi Yang; Haoping Du; Penghao Sun; Ziqi Hou; Chunhua Fu; et al. (Chemical Engineering Journal, 2026)

Curcumin-mediated photodynamic action disturbs TOM70-depedent MIC60 import to damage mitonchondria against breast cancer - Xiang-Yi Zhao; Min Yan; Liang Zheng; Chang-Long Gou; Qi Huang; Liu-Gen Li; Xin-Ran Yu; Jing-Yu Lu; Cui Hu; Si-Han Zhang; Cunqing Kong; Fan Leng; et al. (Journal of Photochemistry and Photobiology B: Biology, 2026)

Hierarchical acceptor engineering of NIR-II butterfly aggregation-induced emission luminogens for enhanced theranostic efficiency - Cheng Lu; Zonghang Liu; Mengli Liu; Zihao Huang; Jianwei Sun; Ryan T.K. Kwok; Tie-Gen Chen; Jacky W.Y. Lam; Ben Zhong Tang (Chemical Engineering Journal, 2026)

Heat Stress Induces Cognitive Impairment Through ACSL4-Mediated Lipid Peroxidation and Subsequent Ferroptosis - Qicheng Zhou; Xinyao Liu; Wenlan Pan; Yicui Qu; Wenjing Shi; Gen Miao; Lu Huang; Xin Li; Mengyu Cai; Hongxia Li; Hui Shen (Molecular Neurobiology, 2026)

Spatial phylogenetics and biocultural conservation of medicinal plants in ethnic minority communities of china: implications for environmental sustainability - Da-Cheng Hao; Yaoxuan Wang; Zhi-Duan Chen; Li-Min Lu; Pei-Gen Xiao (Biodiversity and Conservation, 2026)

Snowflake ZIF-8/Cu2S: A novel adsorbent material for efficient capture of radioactive iodine - Shu-Xuan Li; Xuan Zhao; Yi-Ting Chen; Xiao-Jun Dai; Wen-Ge Zhang; Ao-Tian Gu; Peng Wang; Chun-Hui Gong; Ji-Gen Lu; Yi Yang (Journal of Environmental Chemical Engineering, 2025)

Skeletal and sedimentary structures in yardang caverns in the Mars analog, Qaidam Basin: origin and implication - Qi-Tao Hu; Wen-Ping Liu; Yu-Lu Xue; Qi-Zhi Yao; Sheng-Quan Fu; Yi-Liang Li; Gen-Tao Zhou (CATENA, 2025)

The proteo- and chitinolytic coordinate mechanisms of Streptomyces sp. SCUT-3 and its application in chitinous wastes recycling - Ming-Shu Zhang; Zhi-Wei Li; Lei Wu; Zi-Yang Luo; Can Qin; Fu-Gen Zhang; Chu-Yan Liang; Hai-Ning Wang; De-Lin Lu; Jun-Jin Deng; Xiao-Chun Luo (Chemical Engineering Journal, 2025)

Newly discovered cyanobacteria Nostoc sp. PCC7120 for high efficiency biodegradation of thiamethoxam: Photosynthesis response, enzyme strategies, and molecular mechanisms - Shiye Zhu; Jiale Zhang; Anwei Chen; Youzheng Chai; Jianhua Zeng; Gen Lu; Ma Bai; Jihai Shao; Liang Peng; Si Luo (Bioresource Technology, 2025)

Zinc Ameliorates LPS-Induced Depressive-Like Behaviors Via Modulating Microglial Polarization - ChenQi Li; Gen Miao; Wenjing Shi; Yangjuan Gu; Weiwei Li; Mengyu Cai; Yicui Qu; Yuxiao Tang; Hongtao Lu; Hongxia Li; Hui Shen (Biological Trace Element Research, 2025)

Acetylperoxyl radical-mediated dual oxidative and polymeric pathways for selective bisphenols removal in hypersaline polycarbonate wastewater - Yifan Yin; Delu Miao; Sheping Wang; Zhiyang Gao; Luxin Zhang; Jiaqi Yang; Zhenxin Wang; Jinsuo Lu; Gen Wang (Journal of Environmental Chemical Engineering, 2025)

Removal performance and mechanism of Bi2O3 for radioactive iodine in water: The role of crystal forms and oxygen vacancy - Xiao-Jun Dai; Yi-Ting Chen; Wen-Ge Zhang; Shu-Xuan Li; Ao-Tian Gu; Chun-Hui Gong; Peng Wang; Ji-Gen Lu; Yi Yang (Chemical Engineering Journal, 2025)

Suppression of NRF2 by photodynamic action to enhance bortezomib-triggered DNA damage for synergistic colorectal cancer therapy - Liu-Gen Li; Hao Chen; Ting-Ting Yu; Rui-Lin Liu; Cunqing Kong; Fan Leng; Rong-Cheng Xiao; Yao-Hua Lu; Ning Han; Jun Hu; Yuan-Jian Hui; Tong-Fei Li (Journal of Photochemistry and Photobiology B: Biology, 2025)

Computational design and efficacy assessment of Bufalin-Dendrimer nanoformulation for enhanced cancer therapy - Yurong Sun; Yinhua Lin; Huaitao Sun; Junfa Yang; Hui Cheng; Jia Yi; Wenqiang Li; Gen Lu; Cheng Zhao; Yuge Jiang; Xinyu Zhao; Qinglin Li; et al. (Chemical Engineering Journal, 2025)

Odor impact patterns and health risks of various enterprises in the rubber product manufacturing industry - Yan Zhang; Yan Zhao; Li’an Hou; Zhiyang Zhang; Kehua Zou; Gen Wang; Zhiqiang Lu; Huanwen Cui; Jie Meng; Ting Wu; Jing Wang; Zengxiu Zhai (Journal of Hazardous Materials, 2025)

Promoting adipocyte hyperplasia ameliorates high-carbohydrate diet-induced inflammation, oxidative stress, and metabolic disorders and enhances growth performance and immune function in grass carp (Ctenopharyngodon idellus) - Mingkui Wei; Zhiqi Tian; Niankun Zhang; Lu Zhou; Handong Li; Hong Ji; Gen He; Jianlu Zhang; Jian Sun (Fish Physiology and Biochemistry, 2025)

Breaking the hemicellulose barrier for the preparation of high-performance porous carbon for supercapacitors and Zinc-Ion capacitors - Yang Lu; Gen Zhou; Zhuangzhuang Zhang; Chao Li; Qing Dong; Yinhai Su; Wen Chen (Chemical Engineering Journal, 2025)

Vitamin C alleviates intestinal damage induced by 17α-methyltestosterone in Carassius auratus - Haiyan Zhao; Tongyao Li; Chenyang Li; Zijun Xiong; Weiya Rong; Lu Cao; Gen Chen; Qing Liu; Yu Liu; Xianzong Wang; Shaozhen Liu (Aquatic Toxicology, 2025)

The Enhancing Effect of the East Asian Subtropical Westerly Jet on Summer Extreme High-Temperature Events over Central-Eastern China Since the Late 1990s - Chujie Gao; Yuyu Niu; Gen Li; Shanlei Sun; Bo Lu; Chaofan Li; Bei Xu; Jinglong Huang; Xiubao Sun (Advances in Atmospheric Sciences, 2025)

Growth, biochemical indexes, and intestinal microbiota response of red tilapia (Oreochromis spp.) under different densities and feeding frequencies in the land-based aquaculture tank - Yu-Xiang Xie; Jun-Neng Liang; Gen Kaneko; Lu-Ting Wen; Yi-Jian Li; Qui-Wei Ao; Li-Ming Huang; Qiong Yang; Zhen-Ping Liao; Xue-Ming Yang; Hong-ping Zhang; Lin-Yuan Jiang; et al. (Aquaculture, 2025)

Highly electrostatic cellulose acetate materials assisted by copper ion coordination for air filtration - Ning Yan; Ting Gao; Li Hua; Fan Xie; Rui-Xin Liu; Ding-Gen Hu; Zhao-Qing Lu (Chemical Engineering Journal, 2025)

Innovative coupling pathway for second- and third-generation biomass: Efficient L-lactate synthesis from xylose and C1 compounds - Ya Wu; Gen Lu; Ruiqi Zeng; Zeyang Li; Xin Xu; Yifan Gui; Chonghao Guo; Lizhen Deng; Yutong Bie; Derui Zhang; Yuxin He; Yuyang He; et al. (Chemical Engineering Journal, 2025)

Assessing the Interrelationship Between Microplastics and Polychlorinated Biphenyls Contamination in Chinese Mangrove Sediment - Jianqiao He; Jun Deng; Guochao Zhang; Guoqiang Yi; Gen Peng; Yihua Wei; Lu Ren; Yinghui Wang (Journal of Marine Science and Engineering, 2024)
Mangrove ecosystems, critical intertidal zones at the land–ocean interface, are increasingly recognized for their role in microplastic (MP) pollution dynamics. Despite extensive research on the interaction of MPs with various chemical contaminants, the specific contamination levels of polychlorinated biphenyls (PCBs) associated with MPs in mangroves remain poorly understood. In this study, we quantified the concentrations of PCBs on MPs extracted from representative mangrove sediment samples across China, revealing values ranging from 9.80 to 13.91 ng/g. In contrast, PCB concentrations in sediment samples were found to vary between 25.67 and 69.85 ng/g. Our findings indicate a consistent level of PCB contamination on MPs across different sites, although these levels were marginally elevated compared to those in the surrounding sediments. Notably, Penta-PCBs were detected with the highest frequency across all samples analyzed. This study provides crucial insights into the occurrence and distribution of PCBs on MPs within the mangrove ecosystem, highlighting their significance in environmental contamination assessments.

Deciphering the biodegradation of thiamethoxam by Phanerochaete chrysosporium with natural siderite: Synergistic mechanisms, transcriptomics characterization, and molecular simulation - Shiye Zhu; Anwei Chen; Jiale Zhang; Si Luo; Jizhao Yang; Youzheng Chai; Jianhua Zeng; Ma Bai; Zhenghang Yang; Gen Lu (Journal of Hazardous Materials, 2024)

Correction: A New Safety Control Method of Blasting Excavation in High Rock Slope with Joints - Yingguo Hu; Zhaowei Yang; Shuling Huang; Wenbo Lu; Gen Zhao; Cong Luo (Rock Mechanics and Rock Engineering, 2024)

Constructing efficient Pd/Al2O3 catalyst for reverse water-gas shift via alkali-modification - Xi-Guang Wang; Lu-Yang Qiao; Li-Yuan Xu; Yun-Yun Zeng; Zhi-Shen Huang; Shan-Shan Zong; Jin-Xiang Wang; Zhang-Feng Zhou; Yuan-Gen Yao (Chemical Engineering Journal, 2024)

Deep eutectic solvent for high-performance aluminum-based hydrated eutectic electrolyte - Cheng Lu; Zhilong Wang; Bowen Tao; Ying Wang; Jiaping Sheng; Gen Tang; Yue Wang; Xiang Guo; Jinjin Li; Liangming Wei (Chemical Engineering Journal, 2024)

Tunable sulfur vacancies in amorphous-crystalline AC-Bi2S3-x@C derived from CAU-17 for efficient capture of radioiodine: Comparison of sulfur vacancies in amorphous and crystalline structures - Kai-Wei Chen; Xin-Yu Zhou; Yi-Ting Chen; Xiao-Jun Dai; Shu-Xuan Li; Ao-Tian Gu; Chun-Hui Gong; Peng Wang; Ping Mao; Ji-Gen Lu; Yi Yang (Chemical Engineering Journal, 2024)

Water flush boosts performance of elemental sulfur-based denitrification packed-bed systems: Optimization and mechanisms - Jia-Min Xu; Heng Dong; Hao-Ran Xu; Yi-Lu Sun; Yang Yu; Li-Ying Zhang; Gen-Ping Yi; Wen-Ke He; Chang-Min Wu; Ai-Jie Wang; Hao-Yi Cheng (Bioresource Technology, 2024)

High coking resistance of Ni/A2Ti2O7 catalysts via modulating the A site of A2Ti2O7 (A = La, Gd) for dry reforming of methane - Zheng Liu; Lu-Yang Qiao; Zhang-Feng Zhou; Shan-Shan Zong; Xin-Yi Cao; Jian-Kai Cheng; Yuan-Gen Yao (Fuel, 2024)

Fabrication of stable spherical soybean lipophilic protein nanogel for curcumin delivery: Carbony oxygen and aromatic ring flexibility binding to the beta−barrel - Jianhua Zeng; Junzhe Zou; Lanwei Zhang; Jinlong Zhao; Linlin Liu; Gen Lu; Bingyu Sun; Yanguo Shi; Xiuqing Zhu; Pimin Gong (Food Structure, 2024)

Effects of different stocking densities and feeding frequencies on growth, physiological and biochemical indexes, and intestinal microflora of largemouth bass (Micropterus salmoides) under land-based round pond - Yu-Xiang Xie; Xue-Ming Yang; Gen Kaneko; Jun-Neng Liang; Lu-Ting Wen; Yi-Jian Li; Qui-Wei Ao; Li-Ming Huang; Pan Li; Wen-Wu Min; Lin-Yuan Jiang; Qiong Yang; et al. (Aquaculture, 2024)

Lanostane triterpenoids from the fruiting bodies of Ganoderma amboinense - Li Yang; Guan-Hai Dong; Qing-Yun Ma; Qing-Yi Xie; Jiao-Cen Guo; Jia-Ju Lu; You-Gen Wu; Hao-Fu Dai; You-Xing Zhao (Phytochemistry, 2024)

Ancient terminal water treatment methods still work: Removing micropollutants in drinking water by simultaneous boiling and VUV - Jinsuo Lu; Xingxing Huang; Shiying Li; Yujie Ao; Gen Wang; Haocheng Yang; Zhiqiang Zhang; Heliang Pang; Rui Chen; Qinan Song (Chemical Engineering Journal, 2024)

Accumulation of livestock manure–derived heavy metals in the Hexi Corridor oasis agricultural alkaline soil and bioavailability to Chinese cabbage (Brassica pekinensis L.) after 4-year continuous application - Tian-Xia Guan; Zhao-Ping Lu; Ming Yue; Bao-Guo Li; Ai-Gen Fu; Xu-Dong Zhang; Zhong-Hu Li (Environmental Pollution, 2024)

Pauling-type adsorption of O2 induced reactive oxide species in photocatalytic oxidation by TiOx sensitized Pb-hyperaccumulated biochar - Lei Wang; Yangyang Wang; Jin Liu; Shaofeng Li; Xiaoshu Wang; Xiangxin Lu; Gen Zhang; Ye Li; Jinsheng Wang; Beidou Xi (Chemical Engineering Journal, 2024)

High-performance Cu/Mn modified ceramsite as a persulfate activator to degrade oxytetracycline in batch Erlenmeyer flask and continuous-flow fixed-bed column systems: An exploration of its practicability and non-radical mechanisms - Huang-gen Yang; Mang Lu; Xue-jiao Wu; Rui-ting Dong; Tao-peng Luo; Hui-hua Zhong (Chemosphere, 2023)

Drought shifts soil nematodes to smaller size across biological scales - Leilei Lu; Gen Li; Nianpeng He; Huixin Li; Ting Liu; Xianping Li; Joann K. Whalen; Stefan Geisen; Manqiang Liu (Soil Biology and Biochemistry, 2023)

Asymmetric impacts of El Niño–Southern Oscillation on the winter precipitation over South China: the role of the India–Burma Trough - Xiaohan Lin; Bo Lu; Gen Li; Chujie Gao; Lin Chen (Climate Dynamics, 2023)

Identification of key odor-active compounds and development of odor wheels in rubber product industries using TD/GC-O-MS, OAV, and statistical analysis - Jing Wang; Meng Han; Jie Meng; Gen Wang; Fulei Lu; Zengxiu Zhai; Boyu Jing; Bo Ma; Xiande Xiao; Huanwen Cui; Zhiqiang Lu; Weifang Li (Atmospheric Pollution Research, 2023)

Quantum oscillations in field-induced correlated insulators of a moiré superlattice - Le Liu; Yanbang Chu; Guang Yang; Yalong Yuan; Fanfan Wu; Yiru Ji; Jinpeng Tian; Rong Yang; Kenji Watanabe; Takashi Taniguchi; Gen Long; Dongxia Shi; et al. (Science Bulletin, 2023)

Dispersed Pd/alumina catalyst with finite iodine entry for boosted CO purification and dimethyl carbonate synthesis - Yun-Yun Zeng; Lu-Yang Qiao; Shan-Shan Zong; Rong Guo; Jian-Kai Cheng; Xin-Yi Cao; Zhang-Feng Zhou; Mao-Hong Fan; Yuan-Gen Yao (Chemical Engineering Journal, 2023)

Waste to treasure: Superwetting foam enhanced by bamboo powder for sustainable on-demand oil-water separation - Dong Wu; Shunyou Hu; Beibei Lu; Yuanyuan Hu; Mi Wang; Wen Yu; Gui-Gen Wang; Jiaheng Zhang (Journal of Hazardous Materials, 2023)

Bioaugmentation of intertidal sludge enhancing the development of salt-tolerant aerobic granular sludge - Jin-chi Yao; Gen-ji Yao; Zu-hao Wang; Xin-jie Yan; Qing-qing Lu; Wei Li; Yong-di Liu (Journal of Environmental Management, 2023)

Genetic characteristics of human coronavirus HKU1 in mainland China during 2018 - Xiangpeng Chen; Yun Zhu; Qi Li; Gen Lu; Changchong Li; Rong Jin; Lei Li; Baoping Xu; Liwei Gao; Ju Yin; Zhengde Xie (Archives of Virology, 2022)

Feasibility analyses of virtual models and 3D printing for surgical simulation of the double-outlet right ventricle - Jixiang Liang; Bingheng Lu; Xin Zhao; Jiong Wang; Dianjiang Zhao; Gen Zhang; Bin Zhu; Qiang Ma; Guangyu Pan; Dianyuan Li (Medical & Biological Engineering & Computing, 2022)

Interdecadal change in the influence of El Niño in the developing stage on the central China summer precipitation - Lin Chen; Gen Li; Shang-Min Long; Chujie Gao; Zhiyuan Zhang; Bo Lu (Climate Dynamics, 2022)

Wuzi Yanzong pill attenuates MPTP-induced Parkinson’s Disease via PI3K/Akt signaling pathway - Wei Hang; Hui-jie Fan; Yan-rong Li; Qi Xiao; Lu Jia; Li-juan Song; Yao Gao; Xiao-ming Jin; Bao-guo Xiao; Jie-zhong Yu; Cun-gen Ma; Zhi Chai (Metabolic Brain Disease, 2022)

Grass-livestock balance based grassland ecological carrying capability and sustainable strategy in the Yellow River Source National Park, Tibet Plateau, China - Hui Yu; Bin-tao Liu; Gen-xu Wang; Tong-zuo Zhang; Yan Yang; Ya-qiong Lu; You-xue Xu; Min Huang; Yi Yang; Lv Zhang (Journal of Mountain Science, 2021)

Different Configurations of Interannual Variability of the Western North Pacific Subtropical High and East Asian Westerly Jet in Summer - Xinyu Li; Riyu Lu; Gen Li (Advances in Atmospheric Sciences, 2021)

Inter-annual variability of spring precipitation over the Indo-China Peninsula and its asymmetric relationship with El Niño-Southern Oscillation - Gen Li; Chujie Gao; Bo Lu; Haishan Chen (Climate Dynamics, 2021)

A New Safety Control Method of Blasting Excavation in High Rock Slope with Joints - Yingguo Hu; Zhaowei Yang; Shuling Huang; Wenbo Lu; Gen Zhao (Rock Mechanics and Rock Engineering, 2020)

The Potential Role of PKA/CREB Signaling Pathway Concerned with Gastrodin Administration on Methamphetamine-Induced Conditioned Place Preference Rats and SH-SY5Y Cell Line - Gen-Meng Yang; Lu Li; Feng-Lin Xue; Chen-Li Ma; Xiao-Feng Zeng; Yong-Na Zhao; Dong-Xian Zhang; Yang Yu; Qian-Wen Yan; Yi-Qing Zhou; Shi-Jun Hong; Li-Hua Li (Neurotoxicity Research, 2020)

Toxicity and metabolism of 3-bromopyruvate in Caenorhabditis elegans - Qiao-ling Gu; Yan Zhang; Xi-mei Fu; Zhao-lian Lu; Yao Yu; Gen Chen; Rong Ma; Wei Kou; Yong-mei Lan (Journal of Zhejiang University-SCIENCE B, 2020)

Study on the grossular rabbit with high hardness excavated from Yin Ruins, Anyang, China - Rong Wang; Lu Cai; Tian-tian Bao; Ji-gen Tang; Chang-sui Wang (Archaeological and Anthropological Sciences, 2019)

KDM4B promotes DNA damage response via STAT3 signaling and is a target of CREB in colorectal cancer cells - Wei-Wu Deng; Qian Hu; Zheng-Ren Liu; Qiu-Hong Chen; Wen-Xiang Wang; Huai-Gen Zhang; Qin Zhang; Yuan-Lu Huang; Xue-Kang Zhang (Molecular and Cellular Biochemistry, 2018)

Rebirth after death: forest succession dynamics in response to climate change on Gongga Mountain, Southwest China - Gen-wei Cheng; Xu-yang Lu; Xiao-dan Wang; Jian Sun (Journal of Mountain Science, 2018)

Avian influenza viruses (AIVs) H9N2 are in the course of reassorting into novel AIVs - Hui-ping Chang; Li Peng; Liang Chen; Lu-fang Jiang; Zhi-jie Zhang; Cheng-long Xiong; Gen-ming Zhao; Yue Chen; Qing-wu Jiang (Journal of Zhejiang University-SCIENCE B, 2018)

Neuroprotection and CD131/GDNF/AKT Pathway of Carbamylated Erythropoietin in Hypoxic Neurons - Jing Ding; Jing Wang; Qin-Ying Li; Jie-Zhong Yu; Cun-Gen Ma; Xin Wang; Chuan-Zhen Lu; Bao-Guo Xiao (Molecular Neurobiology, 2017)

Characteristic amino acid changes of influenza A(H1N1)pdm09 virus PA protein enhance A(H7N9) viral polymerase activity - Jun Liu; Feng Huang; Junsong Zhang; Likai Tan; Gen Lu; Xu Zhang; Hui Zhang (Virus Genes, 2016)

Microsatellite records for volume 8, issue 1 - Maria Cristina Arias; Stéphane Aulagnier; Erin F. Baerwald; Robert M. R. Barclay; Jacqueline Silva Batista; Rochelle R. Beasley; Rodrigo A. Bezerra; Frédéric Blanc; Eli S. Bridge; Maria Teresa Cabria; Lívia Izabela Caputo; Jie Chen; et al. (Conservation Genetics Resources, 2016)

Immunotherapy of DC-CIK cells enhances the efficacy of chemotherapy for solid cancer: a meta-analysis of randomized controlled trials in Chinese patients - Xiao-peng Lan; You-gen Chen; Zheng Wang; Chuan-wei Yuan; Gang-gang Wang; Guo-liang Lu; Shao-wei Mao; Xun-bo Jin; Qing-hua Xia (Journal of Zhejiang University-SCIENCE B, 2015)

Identification and gene expression profile analysis of a major type of lipoprotein lipase in adult medaka Oryzias latipes - Lu Wang; Gen Kaneko; Shin-Ichiro Takahashi; Shugo Watabe; Hideki Ushio (Fisheries Science, 2015)

piggyBac transposon-derived targeting shRNA interference against the Bombyx mori nucleopolyhedrovirus (BmNPV) - Fang Zhou; Rui-ting Chen; Yan Lu; Shuang Liang; Mei-xian Wang; Yun-gen Miao (Molecular Biology Reports, 2014)

Dynamic patterns of histone H3 lysine 4 methyltransferases and demethylases during mouse preimplantation development - Gen-Bao Shao; Jun-Chao Chen; Liu-Ping Zhang; Pan Huang; Hong-Yan Lu; Jie Jin; Ai-Hua Gong; Jian-Rong Sang (In Vitro Cellular & Developmental Biology - Animal, 2014)

The metabolism of 8-heptadecene in Pyropia (Bangiaceae, Rhodophyta) - Min Zhang; Rui-Xia Li; Chuan-Ming Hu; Li-En Yang; Jun Tang; Qin-Qin Lu; Tao Zhang; Zong-Gen Shen; Song-Dong Shen; Pu Xu; Jian-Yi Zhu (Journal of Applied Phycology, 2014)

Expression and functions of dopa decarboxylase in the silkworm, Bombyx mori was regulated by molting hormone - Mei-xian Wang; Zi-zheng Cai; Yan Lu; Hu-Hu Xin; Rui-ting Chen; Shuang Liang; Chabungbam Orville Singh; Jong-Nam Kim; Yan-shan Niu; Yun-gen Miao (Molecular Biology Reports, 2013)

Phenol oxidase is a necessary enzyme for the silkworm molting which is regulated by molting hormone - Mei-xian Wang; Yan Lu; Zi-zheng Cai; Shuang Liang; Yan-shan Niu; Yun-gen Miao (Molecular Biology Reports, 2013)

The status of phosphorylated p38 in esophageal squamous cell carcinoma - Shu-tao Zheng; Chuan-shan Zhang; Xu Qin; Yue-hua Gen; Tao Liu; Ilyar Sheyhidin; Xiao-mei Lu (Molecular Biology Reports, 2012)

Role of microRNA let-7 and effect to HMGA2 in esophageal squamous cell carcinoma - Qing Liu; Guo-dong Lv; Xu Qin; Yue-hua Gen; Shu-tao Zheng; Tao Liu; Xiao-mei Lu (Molecular Biology Reports, 2012)

Identification of neutral alleles at pollen sterility gene loci of cultivated rice (Oryza sativa L.) from wild rice (O. rufipogon Griff.) - Jin Quan Li; Muhammud Qasim Shahid; Jiu Huan Feng; Xiang Dong Liu; Xing Juan Zhao; Yong Gen Lu (Plant Systematics and Evolution, 2012)

Genetic Diversity and Identity of Chinese Loquat Cultivars/Accessions (Eriobotrya japonica) Using Apple SSR Markers - Qiao He; Xiong Wei Li; Guo Lu Liang; Kun Ji; Qi Gao Guo; Wei Min Yuan; Gen Zhi Zhou; Kun Song Chen; W. Eric van de Weg; Zhong Shan Gao (Plant Molecular Biology Reporter, 2011)

Abnormal PMC microtubule distribution pattern and chromosome behavior resulted in low pollen fertility of an intersubspecific autotetraploid rice hybrid - Jin-Hua He; Muhammad Qasim Shahid; Zhi-Xiong Chen; Xing-An Chen; Xiang-Dong Liu; Yong-Gen Lu (Plant Systematics and Evolution, 2011)

Effects of hyperoxia on transdifferentiation of primary cultured typeII alveolar epithelial cells from premature rats - Hong-Yan Lu; Gen-Bao Shao; Wen-Bin Li; Hong Wang (In Vitro Cellular & Developmental Biology - Animal, 2011)

Molecular cloning and characterization of twoBrassica napus TTG1 genes reveal genus-specific nucleotide preference, extreme protein-level conservation and fast divergence of organ-specificity - Jun Lu; Jia-Na Li; Bo Lei; San-Gen Wang; You-Rong Chai (Genes & Genomics, 2009)

Novel distribution pattern of fibrinolytic components in rabbit tissues extract: a preliminary study - Xing-guo Lu; Xian-guo Wu; Xiao-hua Xu; Xu-bo Gong; Xuan Zhou; Gen-bo Xu; Lei Zhu; Xiao-ying Zhao (Journal of Zhejiang University-SCIENCE B, 2007)

Cytological mechanism of pollen abortion resulting from allelic interaction of F1 pollen sterility locus in rice (Oryza sativa L.) - Zhi-Sheng Zhang; Yong-Gen Lu; Xiang-Dong Liu; Jiu-Huan Feng; Gui-Quan Zhang (Genetica, 2006)